2021
DOI: 10.1007/s00405-021-07039-2
|View full text |Cite
|
Sign up to set email alerts
|

Mucoepidermoid carcinoma of the head and neck: CRTC1/3 MAML 2 translocation and its prognosticators

Abstract: Purpose Mucoepidermoid carcinoma (MEC) of the head and neck is a prevalent malignant salivary gland tumour with a reported good outcome. The aim of this study was to report the outcome in our centre. Methods A retrospective chart analysis with survival analyses was performed combined with fluorescence in situ hybridization (FISH) analysis to assess CRTC1/3 MAML 2 fusion gene presence. Results Sixty-four cases of MEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
(53 reference statements)
3
4
0
1
Order By: Relevance
“…More recent studies with pathology review to confirm the diagnosis demonstrated a higher frequency of MAML2 translocation in MECs, being 56% to 92.5%. In addition, the presence of fusion did not correlate with histologic grade, recurrence, and/or survival 17,27,32,43–47 . Data from the present study further supported such observations.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…More recent studies with pathology review to confirm the diagnosis demonstrated a higher frequency of MAML2 translocation in MECs, being 56% to 92.5%. In addition, the presence of fusion did not correlate with histologic grade, recurrence, and/or survival 17,27,32,43–47 . Data from the present study further supported such observations.…”
Section: Discussionsupporting
confidence: 76%
“…The literature shows a 5-year DSS of MEC ranging from 95% to 99% 12,23,25,[29][30][31] and a 5-year RFS ranging from 77% to 96%. 10,14,23,25,27 Adverse prognostic factors that are identified previously in MEC and associated with recurrence include high histologic grade, 7,8,10,12,13,16,20,25 nodal metastasis, 8 advanced pT stage, 10,16,20 and PNI. 10 Similarly, we reported larger tumor size, advanced pT stage, LVI, positive surgical margin, and grade as prognostic factors for RFS.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations